Um estudo sobre funções afim e quadrática e métodos algébricos e geométricos para solução de equações do 1º e 2º graus - Freitas, Elizomilson Fonseca (2016)
The teaching of Mathematics has been facing a lot of challenges, mainly when the subject is the hate which some students own about this discipline. The contents about affine and quadratic functions are always seen and exposed in a tradition way and practice, stimulating the students to learn many formulas, in order to find the result in a repetitive way. This paper aims to show a different manner of teaching these contents, giving an extra importance to the algebraic and geometric method, and the utilization of them. It is presented methods of how to solve equations of first and second degrees in a geometric manner, including the method of completing quadrate, by Al-Khwarizmi, which solves geometrically a quadratic equation using areas. To finish this theory, it occurs the exploration and the analysis of the affine and quadratic functions in a dynamic environment (GeoGebra Software). This way, it is aimed in the students the enthusiasm and the pleasure for the Mathematics, turning them into active players of the teaching-learning process.